2012
DOI: 10.1111/j.1365-2966.2012.22010.x
|View full text |Cite
|
Sign up to set email alerts
|

CC Sculptoris: a superhumping intermediate polar

Abstract: We present high-speed optical, spectroscopic and Swift X-ray observations made during the dwarf nova superoutburst of CC Scl in 2011 November. An orbital period of 1.383 h and superhump period of 1.443 h were measured, but the principal new finding is that CC Scl is a previously unrecognized intermediate polar, with a white dwarf spin period of 389.49 s which is seen in both optical and Swift X-ray light curves only during the outburst. In this it closely resembles the old nova GK Per, but unlike the latter ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 42 publications
3
32
0
Order By: Relevance
“…In contrast to RZ Leo, the UV light curve of CC Scl ( Figure 5 top) is completely dominated by the spin modulation of the white dwarf and its harmonic that Woudt et al (2012) only saw during the 2011 November outburst. The DFT (Figure 5, bottom) shows the harmonic of the spin at 194.6 s with a much higher amplitude (220 mma) than the spin period of 389 s (90 mma).…”
Section: Sclmentioning
confidence: 94%
See 4 more Smart Citations
“…In contrast to RZ Leo, the UV light curve of CC Scl ( Figure 5 top) is completely dominated by the spin modulation of the white dwarf and its harmonic that Woudt et al (2012) only saw during the 2011 November outburst. The DFT (Figure 5, bottom) shows the harmonic of the spin at 194.6 s with a much higher amplitude (220 mma) than the spin period of 389 s (90 mma).…”
Section: Sclmentioning
confidence: 94%
“…Longa-Pena et al (2015) confirmed this low value of q from spectroscopy and suggested that CC Scl was a post-period bounce system. Observations with Swift along with ground-based photometry obtained during an outburst in 2011 (Woudt et al 2012) revealed a white dwarf spin period of 389.5 s which was only visible during the outburst. The presence of this spin period identified CC Scl as a member of the intermediate polar (IP) group, 9 systems containing magnetic white dwarfs whose spins are not synchronized with their orbits; see Warner (1995) for a review of IPs.…”
Section: Hubble Space Telescope Ultraviolet Light Curves Reveal Intermentioning
confidence: 98%
See 3 more Smart Citations